Final Report In Search of A Strategy To Build A Field Model To Ensure People's Participation For Sustainable Development: Case Study of the Didayi (A Primitive Tribal Group of Malkangiri District of Orissa) - Planning Commission (Planning Commission, 2002)
Development approach is holistic. It includes both economic and non-economic phenomena in its process. It is a multi-dimensional process. In the development process both economic system and social system are reorganized and reoriented. It encompasses both matena progress and improvement of the quality of life Additional income generation and increase in output in production witness concomitant changes in institutional, socio-cultural and politico-administrative fabrics of a community It does not halt there: further changes are also noticed in people's attitudes, aspirations, ethos ideologies, worldviews and value orientations Precisely, therefore economic development and social development are complementary to each other both in theory and practice Development envisions economic growth and upward social mobility along with social justice.
Case Study of The Didayi
Government of India